Paclitaxel-Coated Balloon Angioplasty for Symptomatic Central Vein Restenosis in Patients With Hemodialysis Fistulas. (February 2015) - Massmann, Alexander; Fries, Peter; Obst-Gleditsch, Kerstin; Minko, Peter; Shayesteh-Kheslat, Roushanak; Buecker, Arno
Purpose: To report a retrospective observational analysis of standard balloon angioplasty (BA) vs. paclitaxel-coated balloon angioplasty (PCBA) for symptomatic central vein restenoses in patients with impaired native hemodialysis fistulas.Methods: A retrospective review was conducted of 27 consecutive patients (15 men; mean age 66±13.8 years, range 39–90) with 32 central vein stenoses (CVS; 6 axillary, 11 subclavian, 12 brachiocephalic, and/or 3 superior caval veins) treated successfully using BA. Freedom from reintervention after BA of de novo lesions was 7.4±7.9 months (range 1–24). Twenty-five (92.6%) patients developed symptomatic restenoses and were treated one or more times by BA (n=32) or PCBA (n=20) using custom-made paclitaxel-coated balloons (diameter 6–14 mm).Results: Technical (<30% residual stenosis) and clinical (functional fistula) success rates for the initial and secondary angioplasty procedures were 100%. No minor/major procedure-associated complications occurred. Mean follow-up was 18.4±17.5 months. Kaplan-Meier analysis for freedom from target lesion revascularization (TLR) found PCBA superior to BA (p=0.029). Median freedom from TLR after BA was 5 months; after PCBA, >50% of patients were event-free during the observation period (mean freedom from TLR 10 months). Restenosis intervals were prolonged by PCBA (median 9 months) vs. BA (median 4 months; p=0.023).Conclusion: Paclitaxel-coated balloon angioplasty of central vein restenosis in patients with hemodialysis shunts yields a statistically significant longer freedom from TLR compared to standard balloon angioplasty.